Nanotechnology-Based Weapons to Combat Human Papillomavirus Infection Associated Diseases - Pan, Luyao; Li, Bingxin; Chen, Jiahua; Zhang, Haofeng; Wang, Xi; Shou, Jiahui; Yang, Dejun; Yan, Xiaojian (Frontiers in Chemistry, 2021)
Persistent human papillomavirus (HPV) infection will eventually lead to clinical problems, varying from verrucous lesions to malignancies like cervical cancer, oral cancer, anus cancer, and so on. To address the aforementioned problems, nanotechnology-based strategies have been applied to detect the virus, prevent the interaction between virus and mammalian cells, and treat the virus-infected cells, due mainly to the unique physicochemical properties of nanoparticles. In this regard, many nanotechnology-based chemotherapies, gene therapy, vaccination, or combination therapy have been developed. In this Minireview, we outline the pathogenesis of HPV infection and the recent advances in nanotechnology-based weapons that can be applied in combating HPV-associated diseases.